Wolves (Canis lupus) in the Toruń Basin (N Poland): actual status and problems concerning the population - Sewerniak, Piotr (Uniwersytet Mikołaja Kopernika w Toruniu, 2015)
The characteristics on the present wolf population of the Toruń Basin were presented in the paper. The subject was introduced in terms of main ecological issues on Canis lupus as well as current problems in man-wolf relations occurring in the region. Forests of the Toruń basin are populated by 25–30 resident wolves which actually live in five packs. For some last seasons the predators have reproduced what is probably the main reason for stated slight increase in wolf number in the region. The major actual threats to local wolf population were indicated: pouching, car traffic and illegal off-road motor activity. In July 2014, the first for the 21st century documented wolf attacks on domestic ungulates were stated in the Toruń Basin when two unprotected from predators cow calves were bite near the Rafa village (NE of Bydgoszcz).